Logistics 4.0 and corporate sustainability: an organizational theory perspective - Vasiulis Ferreira Rodrigues, Nayra; De Camargo Fiorini, Paula; Luiz Piato, Éderson (Revista Gestão da Produção Operações e Sistemas, 2022)
Purpose: The purpose of this paper is to investigate how organizational theories can contribute to understanding the implications of Logistics 4.0 for the sustainable development of corporations. Theoretical framework: The application of Logistics 4.0 technologies can be a great ally in the implementation of measures that aim at sustainable development in organizations. There is evidence in the literature that different organizational theories or perspectives can contribute to understanding the implications of these technologies for corporate sustainability. Design/methodology/approach: A systematic literature review identified 26 eligible articles and applied extensive qualitative data analysis. To analyze the results, Excel software and content analysis were used. Findings: The theories and approaches explored in the studies were the dynamic capabilities view, the diffusion of innovation theory (Bass model), the ecosystem theory, Porter’s value chain theory, and the organization information processing view theory. The findings revealed that Logistics 4.0 enhances organizational capabilities, optimizes scarce and critical resources, and supports the development of sustainable initiatives in the supply chain. Research, Practical & Social implications: This study provides implications by demonstrating possible changes in the logistics industry from an environmental, economic, and social perspective. In addition, the results can be a reference for logistics professionals while driving competitive initiatives in Industry 4.0 and facilitating their strategic decisions. Originality/value: The main contribution of this study is to address the application of several organizational theories to understand how Logistics 4.0 can improve the corporate sustainability, developing a research agenda to steer the progress of the research field. Keywords: Intelligent Logistics; Fourth Industrial Revolution; Industry 4.0; Sustainable Supply Chains; Sustainable Development; Management Theories.